Innovative technology for urban planning and monitoring - Yaakup, Ahris; Sulaiman, Susilawati (2003)
The monitoring of land use change forms an integral part of the urban planning process whereby policies and strategic plans are reviewed and updated. This task typically involves the identification of emerging land use patterns which are normally linked with other planning statistics such as employment, housing and population before the full significance of land use change are apparent. This requires planning programme to be adapted during their implementation as and when incoming information requires such change. Given the dynamic nature of planning and management, it is particularly important to have a well conceived information system, which can serve as the eyes and ears to a regional development planning and monitoring process. This paper will discuss various innovative technology applied to facilitate the urban planning and monitoring process in different administrative levels.